Robust immunoglobulin class switch recombination and end joining in Parp9‐deficient mice. Issue 4 (22nd February 2017) - Robert, Isabelle; Gaudot, Léa; Yélamos, José; Noll, Aurélia; Wong, Heng‐Kuan; Dantzer, Françoise; Schreiber, Valérie; Reina‐San‐Martin, Bernardo
Abstract : Parp9 has been implicated in DNA repair as a reader of ADP‐ribosylation. We show that in Parp9 ‐deficient mice, B‐cell differentiation, class switch recombination, end joining, and T‐cell‐dependent antibody responses are robust. Parp9 is dispensable for the response to DNA damage incurred during the generation and diversification of the B‐cell repertoire in vivo. Abstract : To mount highly specific and adapted immune responses, B lymphocytes assemble and diversify their antibody repertoire through mechanisms involving the formation of programmed DNA damage. Immunoglobulin class switch recombination (CSR) is triggered by DNA lesions induced by activation‐induced cytidine deaminase, which are processed to double‐stranded DNA break (DSB) intermediates. These DSBs activate the cellular DNA damage response and enroll numerous DNA repair factors, involving poly(ADP‐ribose) polymerases Parp1, Parp2, and Parp3 to promote appropriate DNA repair and efficient long‐range recombination. The macroParp Parp9, which is overexpressed in certain lymphomas, has been recently implicated in DSB repair, acting together with Parp1. Here, we examine the contribution of Parp9 to the resolution of physiological DSBs incurred during V(D)J recombination and CSR by generating Parp9 −/− mice. We find that Parp9‐ deficient mice are viable, fertile, and do not show any overt phenotype. Moreover, we find that Parp9 is dispensable for B‐cell development. Finally, we show that CSR and DNA end‐joining are robust in the absence of Parp9, indicating that Parp9 is not essential in vivo to achieve physiological DSB repair, or that strong compensatory mechanisms exist.